The Intelence aNd pRezista Once A Day Study (INROADS): a multicentre, single‐arm, open‐label study of etravirine and darunavir/ritonavir as dual therapy in HIV‐1‐infected early treatment‐experienced subjects - Ruane, PJ; Brinson, C; Ramgopal, M; Ryan, R; Coate, B; Cho, M; Kakuda, TN; Anderson, D (HIV medicine, 2015)
Objectives Following antiretroviral therapy failure, patients are often treated with a three‐drug regimen that includes two nucleoside/tide reverse transcriptase inhibitors [N(t)RTIs]. An alternative two‐drug nucleoside‐sparing regimen may decrease the pill burden and drug toxicities associated with the use of N(t)RTIs. The Intelence aNd pRezista Once A Day Study (INROADS; NCT01199939) evaluated the nucleoside‐sparing regimen of etravirine 400 mg with darunavir/ritonavir 800/100 mg once‐daily in HIV‐1‐infected treatment‐experienced subjects or treatment‐naïve subjects with transmitted resistance. Methods In this exploratory phase 2b, single‐arm, open‐label, multicentre, 48‐week study, the primary endpoint was the proportion of subjects who achieved HIV‐1 RNA < 50 copies/mL at week 48 [confirmed virological response (CVR), non‐virological failure (VF) censored]. Key secondary endpoints included assessments of changes from baseline to week 48 in viral load, immunological response, pharmacokinetics/pharmacodynamics, safety, tolerability, metabolic and bone markers and body fat. Results Forty‐one of the 54 enrolled subjects completed the study. Adverse events (7%) and VF (7%) were the most common reasons for discontinuation. The week 48 CVR rate in the intent‐to‐treat (ITT) non‐VF censored population was 89% (primary endpoint). Seven subjects experienced VF. Common adverse events were diarrhoea (15%), rash (15%) and upper respiratory tract infection (11%). Mild/moderate lipid elevations, minimal changes in limb fat distribution and bone mineral density and no clinically relevant changes in glucose metabolism were observed. Conclusions Etravirine 400 mg and darunavir/ritonavir 800/100 mg as a two‐drug once‐daily regimen in treatment‐experienced subjects or treatment‐naïve subjects with transmitted resistance was virologically efficacious and well tolerated.